Ranibizumab Treatment in Age-Related Macular Degeneration: A Meta-Analysis of One-Year Results - Gerding, H. (Klinische Monatsblätter für Augenheilkunde, 2014)
Background: Although ranibizumab is widely used in age-related macular degeneration there is no systematic data available on the relation between treatment frequency and functional efficacy within the first 12 months of follow-up.Material and Methods: A meta-analysis was performed on available MEDLINE literature. 47 relevant clinical studies (54 case series) could be identified covering 11 706 treated eyes. Non-linear and linear regressions were calculated for the relation between treatment frequency and functional outcome (average gain in visual acuity, % of eyes losing less than 15 letters of visual acuity, % of eyes gaining ≥ 15 letters) within the first year of care.Results: Mean improvement of average visual gain was + 4.9 ± 3.6 (mean ± 1 standard deviation) letters (case-weighted: 3.3 letters). The average number of ranibizumab injections until month 12 was 6.3 ± 2.0 (case-weighted: 5.9). 92.4 ± 3.9 % of eyes (case-weighted: 91.9 %) lost less than three lines of visual acuity and 24.5 ± 8.2 % (case-weighted: 23.3) gained more than 3 lines within the first year. Analysis of the relation between the number of injections and functional improvement indicated best fit for non-linear equations. A nearly stepwise improvement of functional gain occurred between 6.8 and 7.2 injections/year. A saturation effect of treatment occurred at higher injection frequency.Conclusions: The results of this meta-analysis clearly indicate a non-linear relation between the number of injections and functional gain of ranibizumab within the first 12 months of treatment. Treatment saturation seems to occur at a treatment frequency > 7.2 injections within the first 12 months.
Keywords: age-related macular degeneration; AMD; wAMD; nAMD; anti-VEGF; ranibizumab; retina; macula; meta-analysis; review